Lymphedema in Breast Cancer - Muhammad Iqbal; Wirsma Arif Harahap (Journal of Midwifery, 2021)
Forearm edema in breast cancer is caused by disruption of the axillary lymphatic system by surgery or radiotherapy, which causes fluid accumulation in the subcutaneous tissue of the arm, with decreased distensibility of the tissues around the joints and increased weight of the extremities. Risk factors with strong clinical evidence include extensive surgery (eg, axillary lymph node dissection, more dissection of lymph nodes, mastectomy) and being overweight or obese. A BMI greater than or equal to 30 kg / m2 is an independent risk factor for lymphedema associated with breast cancer. Subclinical edema and cellulitis in the literature have also been cited as risk factors for lymphedema associated with breast cancer. The mechanism underlying lymphedema is dysfunction in the lymphatic transport system. of interstitial pressure. Lymphatic fluid, known as lymph, is drained by blind-ended lymphatic capillaries. It is then filtered through the lymph nodes and eventually re-enters the circulatory system, through the thoracic duct, where peripheral venous blood enters the right atrium of the heart. Under normal conditions, the same amount is transported to the interstitial as is transported from the interstitial, a balance that is disturbed in lymphedema due to reduced lymph transport capacity, leading to fluid accumulation and swelling. Options include bioelectrical impedance analysis (BIA), band measurement, perometry, and water displacement. Lymphoscintigraphy, computed tomography (CT) and magnetic resonance imaging (MRI) can also be used to describe lymphatic dysfunction. Management of lymphedema associated with breast cancer conservatively with controlled and operative compression therapy with resection, microsurgery, tissue transfer and liposuction